Industry or relevant market? EMFA and two different perspectives on newspaper concentration - Hellman, Heikki; Grönlund, Mikko; Lehtisaari, Katja; Ranti, Tuomas (Universidad de Navarra, 2025)
When media researchers and policy makers talk about media concentration, they usually mean the concentration of ownership in individual media industries nationwide. When economists and competition authorities talk about media concentration, they mean the concentration of sales or production in the relevant market under consideration. The former, the democratic perspective, emphasises the social and political consequences of concentration, such as the power of large media groups to influence the news agenda. The latter, the market perspective, is concerned with the competitive effects of concentration, such as possible abuse of market power. The article argues that both perspectives are necessary to understand the concentration process, as industry concentration always has market effects and market concentration always has democratic effects. This is also emphasised by the recent European Media Freedom Act (EMFA), which states that when assessing media mergers and acquisitions both the market and the democratic impact of the transaction must be taken into account. The paper demonstrates its argument by analysing newspaper concentration in Finland at both industry (nationwide) and relevant market (region) level in parallel. Employing newspaper net sales as a proxy for market power concentration rate is calculated by using standard measures of concentration. The results show that from the democratic perspective all markets are relevant. While at the regional level the analysis reveals an extremely concentrated market, at the national level the concentration rate is reduced by the large number of firms operating in the sector.